Study of nanostructured ZnO thin films prepared by sol-gel spin-coating technique - Bojorge, Claudia Daniela (2009)
ZnO and ZnO:Al thin films obtained by spin-coating on amorphous SiO2 substrata, were studied by XRR and Gisaxs. Pure ZnO samples showed higher densities and thickness than Al doped one. The thickness of pure ZnO layer films grown linearly with the number of deposits but could not be determined by XRR because of the lack of oscilation in the XRR diagrams being obtained by FESEM. For doped samples the thickness variation with the number of deposit was not significative. The preliminar results about nanopore size, obtained by Gisaxs, were similar.